Bispecific antibody-targeted T-cell therapy for acute myeloid leukemia - Kubicka, Ewa; Lum, Lawrence G.; Huang, Manley; Thakur, Archana (Frontiers in Immunology, 2022)
The management of relapsed or refractory acute myeloid leukemia (AML) continues to be therapeutically challenging. Non-toxic immunotherapy approaches are needed to provide long term anti-leukemic effects. The goal of this study was to determine whether activated T cells (ATC) armed with bispecific antibody (BiAb) could target and lyse leukemic and leukemic stem cells (LSC) without damaging the ability of hematopoietic stem cells to recover or engraft after stem cell transplantation. Anti-CD3 x anti-CD123 BiAb (CD123Bi) and anti-CD3 x anti-CD33GO (gemtuzumab ozogamicin [GO]) BiAb (CD33GOBi) were used to arm ATC to produce Bispecific antibody Armed activated T cells (designated CD123 BATs or CD33GO BATs) to target AML cell lines, peripheral blood mononuclear cells from AML patients and in vivo treatment of AML in xenogeneic NSG mice engrafted with leukemic cells. BATs exhibited high levels of specific cytotoxicity directed at AML cell lines at low 1:1 or 1:2 E:T ratios and secrete Th1 cytokines upon target engagement. Patient samples containing leukemic blasts and LSC when treated with CD33GO BATs or CD123 BATs for 18 hours showed a significant reduction (50-100%; p<0.005) in blasts and 75-100% reduction in LSC (p<0.005) in most cases compared to unarmed ATC. This approach may provide a potent and non-toxic strategy to target AML blasts and LSCs and enhance chemo-responsiveness in older patients who are likely to develop recurrent disease.